Horticultural Building (Max Rigot Selling Co)
One of the most beautiful and restful spots on the World's Fair grounds is found in the gardens adjoining the Horticultural Building. The interior of the building contains a lavish display of landscape gardening and other exhibits of interest to home lovers.